Building Customer Positive e-WOM and Brand Loyalty towards Pet Food in Indonesia - Yunita Wijaya Handranata, Elvin, Monica Anggelia, Olivia Monica (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to investigate factors that are influential towards e-WOM and brand loyalty against pet food in Indonesia, such as brand identification, customer satisfaction and price image. In addition to that, this research also examines the influence of e-WOM toward brand loyalty. The data were obtained by distributing questionnaires in February-April 2020 from 197 respondents who own pets and regularly buys pet food through social media. The data were analyzed using Structural Equation Modeling (SEM). The results showed that brand identification, customer satisfaction, brand loyalty, and price image were significantly correlated with e-WOM, and e-WOM has a significant correlation with brand loyalty. With this research, it is expected that the practice in the field of pet food would better understand the importance of e-WOM and brand loyalty as well as to be able to maximally explore the usage of internet in the field of marketing or product development.